Research of scattering matrix method convergence in the computation problem of quasi-h mode microwave filters - Мамедов, Довлет Байрамович; Ющенко, Александр Георгиевич (Eastern-European Journal of Enterprise Technologies, 2015)
Based on the methods of partial areas and a generalized scattering matrix, an electrodynamic model of the microwave filter design with waveguide-dielectric resonators, partially filling rectangular waveguide by width was constructed. The model allows to consider a countable number of modes in all the problem geometry areas. A numerical algorithm based on the model obtained was implemented and the influence of accounting higher modes on the convergence of the computation algorithm of the amplitude-frequency characteristics of one-, three- and five-tier microwave filters was investigated. The research revealed that at insufficient consideration of harmonics in the area of below-cutoff waveguide, the calculated dependences significantly differ from those to which the experimentally verified algorithm converges, namely, frequency shift and irregularity change of the amplitude-frequency characteristic are observed. The resulting multimode model allows to reduce the error of the intelligent CAD system of the multi-tier filter designs.